1989
DOI: 10.1002/sca.4950110303
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of recently developed correction procedures for electron probe microanalysis

Abstract: Three recently developed absorption and atomic number correction procedures have been investigated with regard to possible improvements and to the performance of these improved models, which has been studied depending on different values of the absorption correction factor. The test file includes 655 measurements of elements with Z > 10 and 258 B-, C-, and Nmeasurements. The results show that the models of Bastin and Heijligers and of Sewell, Love, and Scott generally are substantially better than the one of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Karttunen et al [16] found [19] and further developed by Schiebl [20] (2) According to August [24] this expression, which is similar to that presented by Ruste [25], seems to reflect the physical situation better than other quantifications found in literature. This finding is also proved by the investigations of Sevov et al [4].…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…Karttunen et al [16] found [19] and further developed by Schiebl [20] (2) According to August [24] this expression, which is similar to that presented by Ruste [25], seems to reflect the physical situation better than other quantifications found in literature. This finding is also proved by the investigations of Sevov et al [4].…”
Section: Introductionsupporting
confidence: 72%
“…It quantifies the ratio of the absorption corrections for the secondary fluorescence radiation to that of the primarily generated radiation of a given line of a given element, viz., the excited element. 4.1 THE DEPTH DISTRIBUTION FUNCTION 03A6(03C1z). -As model for the depth distribution function 03A6(03C1z) we chose to take one that is commonly used in electron probe microanalysis, viz.…”
Section: Primary Ionization Intensitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The acceleration energy, however, should not be smaller than x5 keV, because even the best of the commonly used absorption correction models (e.g., [33 to 351) generally are not applicable without restrictions to lower overvoltage ratios or acceleration energies, respectively [36].…”
Section: Experimental Settingsmentioning
confidence: 99%